Pengaruh Implementasi Kurikulum Merdeka terhadap Capaian Pembelajaran pada Materi Keragaman dan Kearifan Lokal Daerah di Sekolah Dasar - Nita Dwi Andayani; Ratna Ekawati; Radeni Sukma Indra Dewi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Education in Indonesia faces various challenges that require curriculum improvement to produce a generation that is intelligent, generous, and capable of competing internationally. The implementation of the Merdeka Curriculum is a strategic step that provides students with the freedom to choose learning materials that align with their interests, thereby enhancing their engagement and understanding. This study aims to analyze the impact of the Merdeka Curriculum on basic competencies and learning outcomes, particularly regarding diversity and local wisdom.The research employs a Systematic Literature Review method, which involves identifying, evaluating, and synthesizing relevant studies. A search in the Google Scholar database yielded 83 relevant articles, from which 13 were selected for in-depth analysis, ultimately narrowing down to five articles that fit the discussion theme. The findings indicate that culture-based and character education not only strengthen individual identity but also preserve cultural heritage and provide practical skills beneficial for students.Overall, it is essential for Indonesia's education system to continuously adapt and innovate to meet contemporary challenges and produce future generations ready to face the world.